(untitled) (Annals of Bangladesh Agriculture, 2025)
Brinjal (Solanum melongena) is a widely cultivated vegetable in Bangladesh, grown year-round. The brinjal shoot and fruit borer (BSFB), Leucinodes orbonalis, is the most destructive pest, causing up to 100% crop loss. Despite the availability of numerous brinjal varieties, none have shown appreciable resistance to BSFB. This study screened 28 brinjal mutant lines for morphological traits to identify genetic resistance to BSFB. Conducted from November 2020 to May 2021 at Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, found no lines resistant to BSFB. However, two lines (G9 and G24) showed tolerance to shoot infestation, while three were susceptible and 22 were highly susceptible. Regarding fruit infestation, no lines displayed resistance, but 10 lines (G1, G3, G9, G14, G15, G18, G19, G23, G24, and G28) exhibited moderate tolerance. Significant variation was observed in plant morphological traits such as plant height, number of primary branches, number of leaves per plant, leaf trichome density, number of leaf spines, shoot diameter, and days to first flowering and fruiting. Positive correlations were found between shoot infestation and plant height and shoot diameter, while negative correlations were observed with the number of primary branches, number of leaves, leaf trichome density, and spine density. Fruit infestation correlated positively with plant height, fruit diameter, weight, and days to first flowering and fruiting and negatively with the number of branches, number of fruits, fruit length, and leaf trichome density. Fruit yield varied significantly, with G6 recording the highest yield and G24 the lowest. Based on these findings, brinjal mutant lines G1, G3, G9, G14, G15, G18, G19, G23, G24, and G28 are recommended for further evaluation to determine their tolerance mechanisms against BSFB at both the morphological and biochemical levels. These findings can assist breeding programs in developing BSFB-resistant brinjal varieties, thereby improving yield and reducing pest damage. Ann. Bangladesh Agric. 28(1): 91-109